Volumetric Mapping of Methane Concentrations at the Bush Hill Hydrocarbon Seep, Gulf of Mexico - Meurer, William P.; Blum, John; Shipman, Greg (Frontiers in Earth Science, 2021)
The role of methane as a green-house gas is widely recognized and has sparked considerable efforts to quantify the contribution from natural methane sources including submarine seeps. A variety of techniques and approaches have been directed at quantifying methane fluxes from seeps from just below the sediment water interface all the way to the ocean atmosphere interface. However, there have been no systematic efforts to characterize the amount and distribution of dissolved methane arounds seeps. This is critical to understanding the fate of methane released from seeps and its role in the submarine environment. This report summarizes the findings of two field studies of the Bush Hill mud volcano (540 m water depth) located in the Gulf of Mexico. The studies were carried out using buoyancy driven gliders equipped with methane sensors for near real time in situ detection. One glider was equipped with an Acoustic Doppler Current Profiler (ADCP) for simultaneous measurement of currents and methane concentrations. Elevated methane concentrations were measured as far away as 2 km from the seep source and to a height of about 100 m above the seep. Maximum observed concentrations were ~400 nmol near the seep source and decreased away steadily in all directions from the source. Weak and variable currents result in nearly radially symmetric dispersal of methane from the source. The persistent presence of significant methane concentrations has implications for helping stabilize exposed methane hydrates. Elevated methane concentrations considerable distances away from seeps potentially provides a much larger methane-promoted biological system than is widely appreciated.